'Afterschool and during vacations': on labor and schooling in the postcolony. Issue 2 (4th March 2019) - Balagopalan, Sarada
ABSTRACT: The Indian state's recent deregulation of child labor, several years after it passed a law making schooling free and compulsory, forces us to attend to the distinct dynamic between child labor and schooling that frame contemporary efforts around compulsory education. This paper opens-up this terrain through historicizing the child-figure – who combines school with wage labor – within the workings of colonial and postcolonial capitalism. It discusses how the strong and continuing traces of a longer history of exclusions is manifest in the widespread global construction of 'school' as inherently 'fungible' or the fragility of the school form, as central to this moment of compulsory schooling. Through a focus on this subaltern child-figure, this paper contends that both the 'fungibility' of schools for marginal children as well as the privatization of child labor foregrounds the antipolitics that undergirds the current fraught working out of compulsory education in the postcolony.